GunDigest Book of CLASSIC COMBAT RIFLES - Wieland, Terry (East Bridgewater, Massachusetts : World Publications Group, Inc., 2013)
The Gun Digest Book of Classic Combat Rifles presents a unique compilation of articles on the greatest American combat rifles developed since 1776, and as they originally appeared in Gun Digest. Since the first edition of Gun Digest in 1994, combat rifles have been a major part of our magazine and book family, with articles on the romance, design, performance, historical, and technical significance-and even the shortcomings-of many rifles used by American troops in battle.
Includes bibliographical references.
Keywords: Rifles -- History; Firearms